2021
DOI: 10.1021/acsaem.1c03405
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Characteristics of InAs Nanowire Networks Directly Grown on Flexible Plastic Substrates

Abstract: III-V semiconductor nanowires have shown promise for thermoelectric applications, but their use in practical devices has conventionally been hindered by complex fabrication processes and device integration. Here, we characterize the thermoelectric properties of InAs nanowire networks directly grown on flexible polyimide plastic. The n-type nanowire networks achieve a high room-temperature Seebeck coefficient of −110.8 μV K −1 and electrical conductivity of 41 S cm −1 , resulting in a thermoelectric power facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Thus, the induced confinement effect can enhance the S value. The presence of unintentionally formed impurity content creates band bending effects at the surface of nanowires fixing the Fermi level above the minima of the conduction band [246]. Prabal Dev Bhuyan et al reported the effect of strain on the transport properties of PdX 2 (X = P, As) nanowires.…”
Section: Dimensionality Effectmentioning
confidence: 99%
“…Thus, the induced confinement effect can enhance the S value. The presence of unintentionally formed impurity content creates band bending effects at the surface of nanowires fixing the Fermi level above the minima of the conduction band [246]. Prabal Dev Bhuyan et al reported the effect of strain on the transport properties of PdX 2 (X = P, As) nanowires.…”
Section: Dimensionality Effectmentioning
confidence: 99%
“…Among III-V compound semiconductors, InAs has drawn special attention due to its small effective mass, high electron mobility and particularly its narrow direct bandgap. Furthermore, InAs NWs have enhanced thermoelectric performance, high Seebeck coefficient at room temperature, over that of bulk InAs, and can be further enhanced using diluted bismide [4][5][6]. Exploiting the use of InAs NWs for thermoelectric generators can efficiently convert heat energy into electrical energy and have possible applications as a coating material on glass/polymer windows for efficient energy harvesting from waste or ambient heat.…”
Section: Introductionmentioning
confidence: 99%